Keith Edmier 1991 - 2007 ; [publ. on the occasion of the exhibition presented at the Center for Curatorial Studies, Bard College, Annandale-on-Hudson, New York, October 20 - February 3, 2008] (Booth-Clibborn Editions, 2007)
Contains molded pink plastic cover with Van Gogh Studio printed on cover; center board with loose red rose, initalled and dated by the artist; Bremen Towne supplement in back cover; Van Gogh Studio photo package containing six photographs in back cover; and a re-creation of the fabric used for Jacqueline Kennedy's pink suit